VILLAGE APPARATUS PERFORMANCE: THE ROLE OF CULTURE, ORGANIZATION SUPPORT AND JOB SATISFACTION? - Sabil, Muhammad Asnawi; Yanto, Heri; Pramono, Suwito Eko; Wijayati, Nanik (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
The performance of village officials has always been a focal point for various parties because the foundation of urban and national progress lies in rural development. However, the performance of village officials in Indonesia is still not optimal. This study aims to investigate the roles of job satisfaction, organizational culture, and perceived organizational support as mediators and moderators in the relationship between competence and performance. The research involved 368 village officials across 19 regencies in West Java province, selected using the inverse root square method. Data collection was conducted through questionnaire distribution using area random sampling methods. Data analysis was performed using Warp PLS method. The findings indicate that job satisfaction successfully mediates the relationship between competence and performance. Organizational culture and perceived organizational support significantly moderate the influence of competence on performance. Village government bodies, village community empowerment agencies, and the Ministry of Villages need to formulate policies that support improving job satisfaction, foster a healthy organizational culture, and provide facilitative support, both in infrastructure and in developing hard and soft skills for village officials.